2021
DOI: 10.3390/ijerph18094494
|View full text |Cite
|
Sign up to set email alerts
|

Mood States and Performance in Elite Canoe Polo Players: The Mediating Role of Stress

Abstract: Sport performance is characterized by competitive stressful conditions that elicit emotional states. The purpose of the study was to examine whether stress mediated the relationship between mood states and performance. Thirty-two elite canoe polo players from four different Italian teams (16 senior males and 16 senior females), aged between 29 and 38 years old (M = 32.3, SD = 2.71), participated in the study. Measures included level of psychological stress, six mood dimensions, and performance outcome. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…These results are in line with the study conducted by Martínez-Gallego et al ( 2022) with 42 male and female tennis players between 12 and 18 years old, Filaire et al (2009) and Keskin et al (2021) with adult tennis players and Wang (2021) with 187 table tennis players in which they showed differences in anxiety-related variables and lower values in self-confidence, although there were no significant differences. Furthermore, they also corroborate the line of Di Corrado et al (2021) in which they demonstrated that female athletes showed higher levels of tension, stress and anger than male athletes, key psychological aspects for sport performance. This may be due to the fact that, when facing the challenge of competition alone, it causes doubts in the sporting performance of these players.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are in line with the study conducted by Martínez-Gallego et al ( 2022) with 42 male and female tennis players between 12 and 18 years old, Filaire et al (2009) and Keskin et al (2021) with adult tennis players and Wang (2021) with 187 table tennis players in which they showed differences in anxiety-related variables and lower values in self-confidence, although there were no significant differences. Furthermore, they also corroborate the line of Di Corrado et al (2021) in which they demonstrated that female athletes showed higher levels of tension, stress and anger than male athletes, key psychological aspects for sport performance. This may be due to the fact that, when facing the challenge of competition alone, it causes doubts in the sporting performance of these players.…”
Section: Discussionsupporting
confidence: 80%
“…In this way, competition generates psychological effects on athletes that counteract their psychoemotional resources ( Flores et al, 2017 ; Coco et al, 2020 ; Jaramillo et al, 2020 ; Di Corrado et al, 2021 ). Likewise, one of these main effects is anxiety, which is characterized by an increase in physiological activity that manifests itself in contexts of high emotional and physical demand, accompanied by the activation of the autonomic nervous system ( Rodríguez et al, 2015 ; Castro-Sánchez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parents also play an important source of influence on their children through the transmission of values, beliefs, and expectations. In addition to providing inspirational messages, credible coaches also structure activities that bring success and improvement of performance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the realm of sports, athletic competitions tend to be inherently anxiety-inducing and feel stressed. For example, previous research conducted by Di Corrado et al (2021) has found that psychological stress in elite canoe polo players plays a fully mediating role in mood and performance. As a result, anxiety has become a prominent area of focus within sports psychology, garnering attention from numerous researchers (Woodman and Hardy, 2003), particularly in relation to anxiety and sports performance.…”
Section: Competitive Anxietymentioning
confidence: 99%